Heterogeneous and hybrid integration for Brillouin microwave photonics - Choon Kong Lai; Moritz Merklein; Alvaro Casas Bedoya; Benjamin J. Eggleton (Advances in Physics: X)
In the rapidly evolving field of integrated photonics, integrated microwave photonics (MWP) stands out as a critical domain for on-chip signal processing applications. Over the past decade, harnessing stimulated Brillouin scattering (SBS) has yielded remarkable progress in this area due to its frequency tunability and unique narrowband resolution that can be achieved in a small footprint. The present article offers a comprehensive review of recent research focused on Brillouin scattering in photonic integrated circuits that guide light and sound, with a specific emphasis on heterogeneous and hybrid integration techniques tailored for applications in microwave photonics. The methodologies for realizing Brillouin hybrid circuits not only enable the seamless integration of Brillouin functions into complementary metal-oxide-semiconductor CMOS-compatible circuits but also facilitate the amalgamation of various active and passive functionalities on a single chip. Our discussion encompasses an overview of the strategies employed in harnessing Brillouin interactions, along with an examination of the associated challenges and limitations. Furthermore, we delve into both the existing and potential applications of this technology within the MWP systems domain, underscoring its multifaceted impact on contemporary research and future technological landscapes.